Gingival Crevicular Fluid Calprotectin, Osteocalcin and Cross-Linked N-Terminal Telopeptid Levels in Health and Different Periodontal Diseases. Issue 6 (21st May 2013) - Becerik, Sema; Afacan, Beral; Öztürk, Veli Özgen; Atmaca, Harika; Emingil, Gülnur
Abstract : Aim: The aim of the present study was to investigate gingival crevicular fluid (GCF) calprotectin, osteocalcin and cross-linked N-terminal telopeptide (NTx) levels in health along with different periodontal diseases. Material and methods: Twenty chronic periodontitis (CP), 20 generalized aggressive periodontitis (G-AgP), 20 gingivitis and 20 healthy subjects were included. Probing depth, clinical attachment level, plaque index and papillary bleeding index was recorded. GCF calprotectin, osteocalcin and NTx levels were analyzed by enzyme-linked immunosorbent assay (ELISA). Results: CP, G-AgP and gingivitis groups had higher GCF calprotectin total amount compared to healthy subjects ( p < 0.008). CP and G-AgP groups had similar, but higher levels compared to gingivitis groups ( p < 0.008). CP and G-AgP groups had lower GCF osteocalcin total amount compared to gingivitis and healthy groups ( p < 0.008). CP group had higher GCF NTx but lower osteocalcin total amount and osteocalcin/NTx ratio than the G-AgP group ( p < 0.008) Conclusions: Our results suggest that elevated GCF calprotectin levels play a role as a reliable inflammatory marker in the pathogenesis of periodontal disease. Fluctuating GCF levels of osteocalcin and NTx might point out to the abnormal bone turnover in periodontitis. Our data document for the first time the role of NTx in the pathogenesis of different periodontal diseases.